Myths, symbols, and rituals in the Bidayuh traditional arts at Bau, Sarawak / Kendy Mitot - Mitot, Kendy (2020)
Bidayuh, formerly known as the Land Dayak, is the fourth largest ethnic group in Sarawak. Ritual ceremonies, traditional arts, tradition, myths and history are equally important to the Bidayuh community. In the past, Bidayuh customary knowledge, cultural worldview and artistic practice were passed down principally as an oral tradition. Their traditional art produces a variety of forms and functions that influence their worldviews and environment. These works of art used for their ritual ceremonies have specific functions and symbolic meanings which connect themselves to their spiritual world. The objective focuses on a Bidayuh's cultural perspective, exploring the intrinsic interpretation from native exegesis elements in the point of view of Bidayuh shamans, whereby the relationship of their ritual ceremonies with traditional art expresses (formalistic contents) especially at Bau, Sarawak. The existences of constitutive, expressive, cognitive symbols and functions have been analysed and interpreted based on a theoretical framework developed by Shawn Wilson’s ‘The Indigenous Research Paradigm’ and by Erwin Panofsky’s ‘Iconology’ through qualitative ethnographic research. Bidayuh culture has their own knowledge in productions of traditional arts such as rasang, sitangor, ba’ie, papan ayun, bisuwi, tipaduak, and togung tikuan that are related to ontological Bidayuh perspectives. Each traditional arts features symbols within their belief system, they have their own specific functions and symbolic meanings that are significant representations of their daily lives, especially connecting themselves spiritually in the rituals ceremony. It is an important foundation towards a sense of the self as well as traditional worldview belief in sustaining traditional arts. Even though each of these traditional arts has a similar form but each of them has a different motif that inspired based on nature and dream of the craftsman’s. It is hoped that further studies can be undertaken on the Bidayuh traditional arts that focus on motifs, meaning and influences from nature and myths. Since the emergence of major religions in Borneo, this ancient tradition rapidly disappeared. Re-contextualization of form and content into systematic documenting classification and contemporary arts could pass down such knowledge and values to communicate narrative storytelling in bringing communities together and keeping these traditions alive.